MODEL PERTUMBUHAN EKONOMI ANTAR KELOMPOK DAN SIMULASINYA - A. L. HERLIANI; E. H. NUGRAHANI; D. C. LESMANA (MILANG Journal of Mathematics and Its Applications, 2009)
Domar’s economic growth model only considers capital as primary variable for production function. On the other hand, Solow’s economic growth model has added the labor as variable in the production function. The aim of this paper is to study distribution model of economic growth among groups in two regions proposed by Zhang (2005). This model considers human capital productivity as one of parameters of the production function. It has been shown that the dynamical system has a unique equilibrium. Therefore, the changes of human capital and propensity to save will influence total capital stocks and capital stocks in each group. Analytically, it is found that an increase in human capital and propensity to save will increase total capital stocks and capital stocks in each group.